A Multipole algorithm for solving a fractional generalization of the helmholtz equation - Belevtsov, N.S. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2021)
The problem of constructing an efficient numerical algorithm for solving a fractional generalization of the Helmholtz equation with the fractional Laplacian is considered. A multipole expansion based on the factorized representation of the fundamental solution of the considered equation is constructed. A numerical method for computing the values of Fox H-functions from the multipole expansion is proposed. A modification of the multipole algorithm for solving the considered fractional generalization of the Helmholtz equation is developed. Numerical results demonstrating the efficiency of the proposed algorithms are discussed.